Using means and methods of general physical training in education of bowlers - Fanigina O.U (Kharkov National Pedagogical University, 2011)
There were discovered the main directions of bowlers education. The means and methods of physical education, which insure the formation of high quality moves being the part of main skill, are discovered. There were shown different means of general education accounting individual peculiarities of bowler. The principles of choosing general developing exercises and main direction of influence on developing different abilities are represented. It's created the scientific-methodic support of physical education in teaching-training process for children who play bowing in sport schools.